In fashion - Stone, Elaine; Farnan, Sheryl A. (Fairchild Books, an imprint of Bloomsbury Publishing Inc, 2017)
"This newest edition of the best-selling In Fashion offers a clear introduction to the fashion industry that is as dynamic as the business itself. Through concise language and full-color photographs, the text provides students with an overview of fashion, from its history, cyclical nature, and development, to the materials, producers, and retailers who impact the business on a global level. Whether their plans include design, product development, merchandising, buying, manufacturing, or entrepreneurship, students will gain a thorough understanding of how the industry works and what lies ahead for them professionally"--Resumé vydavatele
Keywords: móda; módní návrhářství; oděvnictví; fashion; fashion design; clothing trade; učebnice; textbooks